An enhancer sequence in the intrinsically disordered region of FtsZ promotes polymer‐guided substrate processing by ClpXP protease. (11th April 2022) - Viola, Marissa G.; Perdikari, Theodora Myrto; Trebino, Catherine E.; Rahmani, Negar; Mathews, Kaylee L.; Pena, Carolina Mejia; Chua, Xien Yu; Xuan, Botai; LaBreck, Christopher J.; Fawzi, Nicolas L.; Camberg, Jodi L.
Abstract: The essential bacterial division protein in Escherichia coli, FtsZ, assembles into the FtsZ‐ring at midcell and recruits other proteins to the division site to promote septation. A region of the FtsZ amino acid sequence that links the conserved polymerization domain to a C‐terminal protein interaction site was predicted to be intrinsically disordered and has been implicated in modulating spacing and architectural arrangements of FtsZ filaments. While the majority of cell division proteins that directly bind to FtsZ engage either the polymerization domain or the C‐terminal interaction site, ClpX, the recognition and unfolding component of the bacterial ClpXP proteasome, has a secondary interaction with the predicted intrinsically disordered region (IDR) of FtsZ when FtsZ is polymerized. Here, we use NMR spectroscopy and reconstituted degradation reactions in vitro to demonstrate that this linker region is indeed disordered in solution and, further, that amino acids in the IDR of FtsZ enhance the degradation in polymer‐guided interactions.